1997
DOI: 10.1016/s0014-5793(97)00266-4
|View full text |Cite
|
Sign up to set email alerts
|

PHAS‐I phosphorylation in response to foetal bovine serum (FBS) is regulated by an ERK1/ERK2‐independent and rapamycin‐sensitive pathway in 3T3‐L1 adipocytes

Abstract: The phosphorylation state of PHAS-I is thought to be important in the regulation of protein synthesis initiation. PHAS-I phosphorylation significantly increases in response to growth factors and insulin. ERK1/ERK2 have previously been implicated as PHAS-I kinases. Present work utilised a specific phosphorothioate oligonucleotide antisense strategy against ERK1/ERK2 to determine whether ERK1/ERK2 mediate FBSstimulated PHAS-I phosphorylation in vivo. Depleting > 90% of cellular ERK1/ERK2 had no effect on FBS-sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In studies of 3T3-L1 cells show C/EBP-ββ and C/EBP-α δ are expressed before and activate the transcription of these master regulators PPAR-γ and C/EBP-α. Several studies have been reported that extracellular signal-regulated kinases (ERK) and Akt pathway play essential roles in adipogenesis [11][13]. From these studies showed that ERK1/2 phosphorylation had an important role in early stage of adipocytes differentiation [14].…”
Section: Introductionmentioning
confidence: 99%
“…In studies of 3T3-L1 cells show C/EBP-ββ and C/EBP-α δ are expressed before and activate the transcription of these master regulators PPAR-γ and C/EBP-α. Several studies have been reported that extracellular signal-regulated kinases (ERK) and Akt pathway play essential roles in adipogenesis [11][13]. From these studies showed that ERK1/2 phosphorylation had an important role in early stage of adipocytes differentiation [14].…”
Section: Introductionmentioning
confidence: 99%
“…Together, these results suggest that basal cells possess a constant level of kinase activity that is actively suppressed by the action of PPases. Arnott et al (25) reported that serum-induced PHAS-I phosphorylation is independent of the ERKlERK2 pathway in 3T3-Ll adipocytes. We previously showed (9) that inhibition of MAPK and ~7 0 '~~ greatly reduced Prl-mediated Nb2 protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the ERK1/ ERK2 cascade is a well established post-receptor response to insulin treatment. The effect of ␣AS1 treatment on insulinstimulated ERK2 activation was measured by band shift on anti-ERK2 Western blots (17). An insulin concentration was chosen that activated Ͻ50% of the cellular ERK2 pool, such that any augmentation in ERK2 activation caused by PTP␣ depletion would be detected.…”
Section: Development and Characterization Of An Antisense Strategy Fomentioning
confidence: 99%